Directional lasing in resonant semiconductor nanoantenna arrays - Ha, Son Tung; Fu, Yuan Hsing; Emani, Naresh Kumar; Pan, Zhenying; Bakker, Reuben M.; Paniagua-Domínguez, Ramón; Kuznetsov, Arseniy I. (Nature nanotechnology, 2018)
High-index dielectric and semiconductor nanoparticles supporting strong electric and magnetic resonances have drawn significant attention in recent years. However, until now, there have been no experimental reports of lasing action from such nanostructures. Here, we demonstrate directional lasing, with a low threshold and high quality factor, in active dielectric nanoantenna arrays achieved through a leaky resonance excited in coupled gallium arsenide (GaAs) nanopillars. The leaky resonance is formed by partially breaking a bound state in the continuum generated by the collective, vertical electric dipole resonances excited in the nanopillars for subdiffractive arrays. We control the directionality of the emitted light while maintaining a high quality factor ( Q = 2,750). The lasing directivity and wavelength can be tuned via the nanoantenna array geometry and by modifying the gain spectrum of GaAs with temperature. The obtained results provide guidelines for achieving surface-emitting laser devices based on active dielectric nanoantennas that are compact and highly transparent. Active dielectric nanoantenna arrays exhibit low-threshold and high-quality-factor directional lasing achieved via a leaky resonance excited in coupled gallium arsenide (GaAs) nanopillars.